Planning the Transfer of a 20 kV Distribution Feeder from Mariana Substation to Tanjung Api-Api Substation for Makarti Jaya Village - Kms. Andi; Andri Riyana; Subianto Subianto (Jurnal Ilmu Siber dan Teknologi Digital, 2025)
Purpose: The rapid population growth and increasing electricity demand in Makarti Jaya Village, Banyuasin Regency, have pushed the Tomato Feeder at Mariana Substation close to its capacity limit. This study designs a medium-voltage feeder transfer by redirecting supply from the near-overloaded Tomato Feeder to the idle Ferry Feeder at Tanjung Api-Api Substation. Methodology: A documentary research approach was used based on technical data from PT PLN (Persero), including feeder loading, substation capacity, and network configuration. Engineering calculations were conducted using SPLN 41-8:1981, AVE D210, and PLN design standards to determine pole requirements, conductor sizing, sag, voltage drop, and voltage regulation.Results: The proposed 20 kV network requires 642 reinforced concrete poles with AAAC 70 mm² conductors over 96.915 km. The calculated voltage drop is 685.44 V with a voltage regulation of 3.55 percent, remaining within PLN’s ±5 percent standard. Conclusions: The feeder transfer is technically feasible, reduces system loading, shortens network distance significantly, and maintains acceptable voltage quality.Limitations: This study focuses only on technical engineering design and does not include economic feasibility analysis, protection coordination, environmental impact assessment, or long-term load growth forecasting.Contributions: This study provides a structured engineering framework for medium-voltage feeder transfer planning in rural electrification systems, including systematic procedures for pole calculation, conductor selection, sag estimation, and voltage performance evaluation based on PLN standards.